2009
DOI: 10.1007/s00127-009-0021-9
|View full text |Cite
|
Sign up to set email alerts
|

A community-based study of case fatality proportion among those who carry out suicide acts

Abstract: Suicide method and older age are independent predictors of the fatality of suicide acts. Suicide prevention strategy and clinical assessment ought to take into account of these two factors. Diminution of pesticide toxicity and control of access to pesticides are important considerations for suicide prevention in rural Taiwan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 17 publications
2
26
0
Order By: Relevance
“…In most studies, male sex has been associated with higher mortality rates due to suicide,3,36 while female sex has been linked to a higher incidence of repeat suicide attempts 18. A discrepancy regarding the rate of repeat suicide attempts between sexes exists among previous international studies 22,37. Social environment and cultural differences might be important factors accounting for the conflicting results 38,39.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In most studies, male sex has been associated with higher mortality rates due to suicide,3,36 while female sex has been linked to a higher incidence of repeat suicide attempts 18. A discrepancy regarding the rate of repeat suicide attempts between sexes exists among previous international studies 22,37. Social environment and cultural differences might be important factors accounting for the conflicting results 38,39.…”
Section: Discussionmentioning
confidence: 99%
“…Following previous epidemiology research,20,22,26 individuals who attempted suicide were classified into two groups based on the lethality of their suicide method. The first, the low-lethal group, consisted of those who attempted suicide through poisoning by solid or liquid substances (E950) or used cutting and piercing instruments (E956).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For geographic and demographic subgroups, the CFR is determined largely by the distribution of methods used in suicidal acts, rather than by marked variation in method-specific case fatality across subgroups (28,40,56,87,113). For example, compared with females, males are less likely to engage in suicidal behavior (and only slightly more likely to die by suicide when they use a given method), but three to four times more likely to die in a suicidal act because the methods that men use are far more lethal (56,87,113).…”
Section: Determinants Of the Case Fatality Ratiomentioning
confidence: 99%
“…For methods of high lethality, such as hanging and jumping, men and women did not differ significantly in case fatality. One prior study from rural Taiwan has demonstrated no gender differences in case fatality when variables such as age and suicide method were considered 23. Pesticide, an agent of high lethality, is the most commonly used substance in solid/liquid poisoning in rural Taiwan; conversely, medication overdose, a method of low lethality, is the most common agent used for solid/liquid poisoning suicide in metropolitan Taipei.…”
Section: Discussionmentioning
confidence: 97%